Structural design for hazardous loads : the role of physical testing - Clarke, J. L.; Garas, F. K.; Armer, G. S. T.; Institution of Structural Engineers (Great Britain); Great Britain. Building Research Establishment; International Seminar on Structural Design for Hazardous Loads (1991 : Brighton, UK) (London : E & FN spon, 1992)
09